Anthropometric Measurements as an Indicator of the Level of School Health for Students in Some Basic Education Schools in the City of Nalut - Aborus, Naji; Gnan, Nargis; Mshaikh, Hajar; Al Khmaisy, Retaj (Sharwes Scientific Journal, 2025)
The study aimed to evaluate the health level of a sample of students in primary schools in Nalut city for the year 2023/2024, by calculating anthropometric measurements (body mass, height, waist, body surface area, and body mass index). Growth charts were also used for males and females. The study sample consisted of 315 primary school students aged ten to thirteen years, who were randomly selected from 14 schools under the supervision of Nalut city education. The data were analyzed using the arithmetic mean and standard deviation. The t-test was used at a significance level of p ≤ 0.05, and Pearson’s correlation coefficient for some factors. The results showed that the body mass index (BMI) ranged between 11.6-36.2 with an arithmetic mean of 19.7. The results also showed that 47.6% of students had weights below the normal range. 10.2% were above the normal range, while 32.7% had weights within the normal range. The results of the statistical analysis showed that the gender variable had a statistically significant effect at the significance level (P≤ 0.05) on height and body surface area in favor of females compared to males. The average waist for males was 63.35 cm, while for females it was 62.50 cm. The results showed that females were less than males by a statistically significant difference. The study also showed a strong positive correlation and a direct relationship between BMI and Body Surface Area (BSA), where the value of Pearson’s correlation coefficient r = 0.873. It also showed a strong correlation and a direct relationship between the variable of students’ weight and the body surface area BSA. The value of Pearson’s correlation coefficient r = 0.818.